Anti-federal sentiment in Sabah and its impact on Malaysian politics - Mohammad Azziyadi Ismail,; Mohammad Agus Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The conflict between the federal government and the state of Sabah has occurred since 1963 stemming from the dissatisfaction of the people of Sabah towards the implementation of their autonomy rights as contained in the 1963 Malaysia Agreement (MA63). This dissatisfaction led to an anti-federal sentiment among the people of Sabah towards the federal government, which threatened the stability of the Federation of Malaysia. Hence, this study examines the factors leading to the emergence of anti-federal sentiment in Sabah and assesses the impact of such sentiment on Malaysian politics utilising the concept of federalism as an analytical tools. The primary source of this artile comprised interviews, whereas books, journals, official government reports, articles and news portals were used as its secondary sources. Findings revealed that the factors promoting the anti-federal sentiment among Sabahans are thedissatisfaction with the implementation of autonomy rights and MA63, the imbalance in infrastructure development, the socio-economic gap between Sabah and the states in the Peninsula, distribution of oil royalties and the presence of illegal immigrants. This anti-federal sentiment has createda strained relationship between the federal government and Sabah, the demand for self-government, the fading of patriotism, the threat to national harmony and unity, the rise of state nationalism and the decline of the people’s nationalism. Consequently, this sentiment threatens the stability of the federation and therefore requires an immediate solution to maintain national unity and sovereignty.